The Transient Display of a Chimeric PD-L1 Protein on Pancreatic Islets Promotes Indefinite Survival in Allogeneic Recipients. (July 2018) - Batra, Lalit; Shrestha, Pradeep; Yolcu, Esma S; Zhao, Hong; Bowen, William S; Woodward, Kyle B; Coronel, María M; Tan, Min; García, Andrés J; Shirwan, Haval
Abstract : Introduction and Objective: Allogenic islet transplantation is an important therapeutic approach for the treatment of Type 1 Diabetes (T1D). However, graft rejection initiated and perpetuated by pathogenic T effector (Teff) cells presents a major barrier. One approach that has proven successful for promoting graft tolerance is shifting the T cell balance away from the induction of pathogenic Teff cells and towards the generation of protective T regulatory (Treg) cells. PD-1/PD-L1 immune checkpoint pathway plays an important role in the Teff and Treg balance with demonstrated clinical efficacy in cancer immunotherapy. The goal of this study was to assess the immunoregulatory function of PDL1 in controlling the rejection of allogeneic islets grafts. Materials and Methods: A DNA construct encoding the extracellular portion of PD-L1 protein fused to a modified form of core streptavidin was generated. The chimeric SA-PDL1 protein was produced in insect cells, purified using immunoaffinity columns, and characterized for structure. The function of SA-PDL1 was assessed in vitro for the conversion of Teff into Treg cells, and its capacity to suppress Teff proliferation in response to allogeneic stimulation. For in vivo studies, BALB/c islets were modified with biotin followed by engineering with SA-PDL1 protein (~200 ng/1000 islets). Engineered islets (~500 islets/transplant) were then transplanted under the kidney capsule of streptozotocin-induced diabetic C57BL/6 mice under transient cover of rapamycin (0.2 mg/kg) administered daily for 15 days starting the day of transplantation. Groups with unmodified pancreatic islets and rapamycin treatment or SA-PDL1-engineered islets without rapamycin treatment served as controls. Results and Discussion: SA-PDL1 was successfully expressed and purified. In vitro, the protein enhanced TGF-beta-induced conversion of Teff into Treg cells and effectively suppressed the proliferation of Teff cells in response to alloantigen stimulation. In vivo, SA-PDL1-engineered BALB/c islet grafts, with concurrent rapamycin treatment, remained functional for over a 100-day observation period. In marked contrast, unmodified islets, under the same rapamycin regimen, were acutely rejected within 20 days. SA-PDL1-engineered islets without rapamycin showed prolonged survival, although all grafts were eventually rejected within 40 days. Conclusion: These results provide strong proof-of-efficacy and feasibility for the use of SA-PDL1 protein as an immunomodulator to promote allogeneic islet graft survival in the absence of continued immunosuppression. This study was funded in part by NIH (grants R21EB020107, R21AI113348, 185 R56AI121281, and F30AR069472).